Some prosodic aspects in Kannada - H M, Nandini (Journal of All India Institute of Speech and Hearing, 2020)
Speech is defined as the concurrent motor functions of respiration, phonation, resonance and articulation prosody. Prosody has been viewed as decorative ornamentation, functioning to make speech more aesthetically pleasing. Intonation is one aspect of prosody, other aspects being stress and rhythm.